Zakat, Islamic Virtues, and Social Justice: A Case of the Chiang Mai Zakat (Bayt al-Māl) Fund in Chiang Mai Province of Thailand - Laila Rimpeng (Al-Jami'ah: Journal of Islamic Studies, 2022)
This research aimed to study Islamic virtues underlying the reform and practice of the Chiang Mai Zakat (Bayt al-Māl) Fund to promote social justice in Muslim communities Chiang Mai Province, Thailand. Data were collected through in-depth interviews with its key figures including three advisors, three administrative members and one supporting staff. Non-participatory observation was also conducted on its activities between 2017 and 2018. The data were analyzed to find out about religious motivation and understandings behind the organizational reform and practice. Findings showed that three Islamic virtues of amānah, ikhlās and ukhūwah provided a guiding framework for the Chiang Mai Zakat (Bayt al-Māl) Fund in its effort to meet the social goal of the Islamic prescription of zakat and respond to needs of underprivileged Muslims. [Artikel ini membahas keutamaan nilai Islam pada konteks reformasi dan praktik dari rumah zakat Chiang Mai dalam mempromosikan keadilan sosial pada komunitas muslim di Provinsi Chiang Mai, Thailand. Data dikumpulkan melalui wawancara mendalam pada tokoh kunci lembaga seperti; penasehat, staf administrasi dan staf pembantu. Pengamatan lapangan dilakukan antara 2017-2018. Kesimpulan analisisnya menunjukkan bahwa pemahaman dan motivasi agama menjadi landasan praktik dan reformasi organisasi. Amanah, ikhlas dan ukhuwah merupakan tiga nilai yang menjadi kerangka panduan lembaga zakat Chiang Mai dalam mempertemukan nilai sosial wajib zakat dengan kelompok muslim yang kurang mampu secara ekonomi.]